Pengaruh Peran Kepala Madrasah Sebagai Manajer dan Supervisor Terhadap Profesionalisme Guru MA Al Amiriyyah Blokagung Banyuwangi - Komarudin A; Vivi Indah Lestari (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
This research is directed at 3 main points, namely (1) is there an influence on the role of the madrasa head as manager on the professionalism of MA Al Amiriyyah Blokagung Tegalsari Banyuwangi 2019/2020 academic year (2) is there any influence on the role of the madrasah head as supervisor on the professionalism of MA Al Amiriyyah Blokagung teachers Tegalsari Banyuwangi 2019/2020 academic year (3) is there any influence of the role of the madrasa head as manager and supervisor on the professionalism of MA Al Amiriyyah Blokagung teachers Tegalsari Banyuwangi 2019/2020 academic year. This study uses quantitative methods with product moment techniques in the validity of the data and to find the reliability of the data using the alpha formula, while in the hypothesis test using the F test and P test then using multiple regression models. The population of this study was 40 Al Amiriyyah MA teachers. To measure variables, researchers use questionnaires for facilities and infrastructure and teacher performance. After analyzing the data collected, it was found that (1) the role of the madrasa head as a manager did not affect the professionalism of MA AL Amiriyyah Blokagung Tegalsari Banyuwangi teacher year 2019/2020. (2) the role of the madrasa head as a supervisor affects the professionalism of the MA AL Amiriyyah Blokagung Tegalsari Banyuwangi teacher in the 2019/2020 academic year. (3) factors influencing the professionalism of MA Al Amiriyyah Blokagung Tegalsari banyuwangi teachers are only the role of the madrasah head as supervisor.